COMPETENCE APPROACH IN PSYCHOLOGICAL AND PEDAGOGICAL TRAINING OF FUTURE LAWYERS - Котикова, О. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted to the problems of formation psychological and pedagogical competence of future lawyers. The article describes components of psychological and pedagogical competence of future lawyers and its content in different periods of their psychological and pedagogical training. The author analyzes the possibility of applying the competency approach in psychological and pedagogical training of future lawyers, justifies components of their psychological and pedagogical competence in different periods of their psychological and pedagogical training. The findings allow determine the parameters of such competence and application of competence approach in psychological and pedagogical training of future lawyers